(untitled) (Texas Journal of Medical Science, 2026)
To analyze the pathomorphological and immunohistochemical characteristics, as well as modern aspects of the histogenesis of cardiac myxoma, and to systematize the criteria for differential diagnosis with other intracardiac formations.